Post-traumatic stress symptoms and burnout in healthcare professionals working in neonatal intensive care units: Results from the STRONG study - Ravaldi, C.; Mosconi, L.; Mannetti, L.; Checconi, M.; Bonaiuti, R.; Ricca, V.; Mosca, F.; Dani, C.; Vannacci, A. (Frontiers in Psychiatry, 2023)
Background: Newborns’ deaths and life-threatening conditions represent extremely stressful events for parents and professionals working in NICUs, facilitating the onset of secondary traumatic stress symptoms. The STRONG study aims to better understand the psychological impact on Italian NICUs staff of bereavement care. Methods: The STRONG (STress afteR lOss in NeonatoloGy) study is a cross-sectional study based on a web survey consisted of four sections: sociodemographic, CommuniCARE-Newborn questionnaire, the Maslach Burnout Inventory and the Impact of Event Scale-Revised. Results: 227 NICU workers (42.7% nurses, 23.3% midwives, 22.2% physicians, 11.8% other HCPs) answered the survey. The hardest tasks were “communicating baby’s death” and “informing on autopsy results”; 44.7% of HCPs did not receive formal training in communicating bad news, 44.2% ‘learned from the field’ by watching other colleagues; 41.2% declared that they do not have any communication strategy. More than 90% of professionals thought that training on bereavement care is necessary. The majority of HCPs showed some degree of post-traumatic stress symptoms: 34% medium and 35.3% severe. Professionals with training in bereavement care and/or in communication had less probability to develop stress symptoms. A multivariate analysis showed that higher levels of burnout were associated with 4 or more monthly losses and medium or severe stress symptoms. Having a well-defined communication strategy for breaking bad news was independently associated with a better personal accomplishment. Conclusions: Dealing with newborns’ deaths is a highly stressful task; professionals should receive proper support such as debriefing, psychological support and training in order to prevent post-traumatic stress symptoms and reduce professional burnout.